2023
DOI: 10.1002/eap.2887
|View full text |Cite
|
Sign up to set email alerts
|

High‐latitude invasion and environmental adaptability of the freshwater mussel Limnopernafortunei in Beijing, China

Abstract: The invasive freshwater mussel Limnoperna fortunei (Dunker, 1857) has spread widely throughout Asia and South America, especially via interbasin water diversion and navigation. The middle route of the South‐to‐North Water Transfer Project (SNWTP), whose terminal is Beijing, has diverted more than 60 billion m3 of water from the Yangtze River Basin to Northern China since December 2014. L. fortunei has spread north to Beijing along the SNWTP, biofouling its channels and tunnels. To determine the status of L. fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…They also identified a key control period to reduce further spread and mitigate negative impacts. Wang, Xu, et al (2023) also focused on this invasive mussel and investigated the environmental variables responsible for the survival of veligers at different developmental stages in the invasion front in Beijing. Their study showed that controlling early-stage veligers through adjustments in water temperature, pH, and food size could effectively limit further spread.…”
Section: Risk Analysismentioning
confidence: 99%
“…They also identified a key control period to reduce further spread and mitigate negative impacts. Wang, Xu, et al (2023) also focused on this invasive mussel and investigated the environmental variables responsible for the survival of veligers at different developmental stages in the invasion front in Beijing. Their study showed that controlling early-stage veligers through adjustments in water temperature, pH, and food size could effectively limit further spread.…”
Section: Risk Analysismentioning
confidence: 99%